Complete chloroplast genome sequencing of sago palm (Metroxylon sagu Rottb.): Molecular structures, comparative analysis and evolutionary significance - Chung, Hung Hui; Lim, Leonard Whye Kit; Hasnain, Bin Hussain (Elsevier, 2020)
The sago palm (Metroxylon sagu Rottb.) is an underappreciated essential food crop of the century and is deemed to be the ultimate solution to future food security issues globally. To grasp a better comprehension on the molecular basis of sago palm chloroplast, a complete characterization of the 157,300 bp chloroplast genome sequences (encompassing 85,257 bp large single copy region (LSC) and 17,533 bp small single copy region (SSC), sandwiched by a pair of 27,245 bp inverted repeats (IRs)) was performed. The genome houses 113 unique genes: 80 protein-coding genes, 29 tRNA genes and four ribosomal genes. The gene order, AT content and orientation of the M. sagu chloroplast genome closely resembles that of its congeneric species, M. warburgii. The distribution patterns of short and long repeats were also determined along with four highly variable regions, 216 mutation events (164 single nucleotide polymorphisms (SNPs) and 52 insertion/deletions (indels)) between the two Metroxylon genus members. The maximum likelihood phylogenetic tree had unravelled the close relationship of M. sagu, with its closest neighbour M. warburgii, together with other Calameae members like Pigafetta elata, Calamus caryotoides, and Salacca ramosiana. This study had dissected on the entire chloroplast genome of M. sagu and characterized the contents at the molecular level. It is anticipated that the yielded treasurable information will be channelled for species identification and evolutionary analysis within the Metroxylon genus in future.